2021
DOI: 10.1186/s13019-021-01714-5
|View full text |Cite
|
Sign up to set email alerts
|

Double arterial cannulation versus right axillary artery cannulation for acute type A aortic dissection: a retrospective study

Abstract: Background Cannulation strategy in surgery for acute type A aortic dissection (ATAAD) remains controversial. We aimed to retrospectively analyze the safety and efficacy of double arterial cannulation (DAC) compared with right axillary cannulation (RAC) for ATAAD. Methods From January 2016 to December 2018, 431 ATAAD patients were enrolled in the study. Patients were divided into DAC group (n = 341) and RAC group (n = 90). Propensity score matching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In terms of postoperative liver and renal function, we compared ALT and creatinine levels at 1 and 3 days after surgery, respectively. Zhang et al 14 reported DAC reduced the incidence of postoperative renal injury compared to AAC, suggesting it might be benefit for renal protection. However, postoperative creatinine levels were similar in two groups in our study, indicating DAC was similar to AAC in protecting renal function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of postoperative liver and renal function, we compared ALT and creatinine levels at 1 and 3 days after surgery, respectively. Zhang et al 14 reported DAC reduced the incidence of postoperative renal injury compared to AAC, suggesting it might be benefit for renal protection. However, postoperative creatinine levels were similar in two groups in our study, indicating DAC was similar to AAC in protecting renal function.…”
Section: Discussionmentioning
confidence: 99%
“…27 Moreover, it may enhance renal perfusion and reduce the risk of renal impairment following surgery in comparison with other cannulations. 14,22 However, the inherent disadvantages include retrograde brain flow, the risk of malperfusion, and possible damage to the artery, which is located far from the lower extremity of the vasculature. The brain perfusion suggested DAC provided better brain protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some known advantages of double artery cannulation include stabilization of CPB flow, avoidance of the overuse of large cannulas on the axillary artery, prevention of the retrograde perfusion that occurs with single femoral artery cannulation, and a shorter cooling period ( 17 ). The application of bilateral artery perfusion has been shown not to increase the surgical risks compared to RAA cannulation but could help reduce the incidence of postoperative AKI ( 18 ). In this situation, femoral cannulation can increase visceral perfusion and compensate for the partial blood to the celiac and superior mesenteric arteries, as the intimal flap motion block in the AAD model is perfused only by axillary cannulation ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Each method has distinct effects on patient survival, cerebral perfusion, and malperfusion hazards [11,24]. The significance of individualized decision-making in AAD surgery is highlighted by the fact that the choice depends on anatomical considerations, surgeon expertise, and patient factors.…”
Section: Comparative Analysis Of Outcomes and Considerations For Each...mentioning
confidence: 99%